Ribosome-Induced Cellular Multipotency, an Emerging Avenue in Cell Fate Reversal - Arif Istiaq; Kunimasa Ohta (Cells, 2021)
The ribosome, which is present in all three domains of life, plays a well-established, critical role in the translation process by decoding messenger RNA into protein. Ribosomal proteins, in contrast, appear to play non-translational roles in growth, differentiation, and disease. We recently discovered that ribosomes are involved in reverting cellular potency to a multipotent state. Ribosomal incorporation (the uptake of free ribosome by living cells) can direct the fate of both somatic and cancer cells into multipotency, allowing them to switch cell lineage. During this process, both types of cells experienced cell-cycle arrest and cellular stress while remaining multipotent. This review provides a molecular perspective on current insights into ribosome-induced multipotency and sheds light on how a common stress-associated mechanism may be involved. We also discuss the impact of this phenomenon on cancer cell reprogramming and its potential in cancer therapy.